The Effect of Five Finger Therapy on Hypertension Elderly on Anxiety Reduction - Dian Fazira Khoirunisa; Qurrotul Aeni; Andriyani Mustika Nurwijayanti; Triana Arisdiani (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Five finger therapy is a relaxation technique using the five fingers technique by relying on positive thoughts to help reduce anxiety in people with chronic hypertension. This study was to determine the level of anxiety before being given five finger therapy pain management and after being given five finger therapy pain management and the effect of giving five finger therapy management to reduce anxiety levels in patients with chronic hypertension. This research is a Quasy Experiment quasi-experimental research with One Group Design Pretest – Posttest design, quantitative research type. The sample of this research is 56 respondents with consecutive sampling technique. the results showed that the majority of respondents experienced a decrease in anxiety levels before and after being given 5-finger therapy. Statistical analysis test using T-test. From the research results obtained p value is 0.000. This value is smaller than 0.05 (p < 0.05). Based on these results, it means that there is an effect of 5 finger therapy management on reducing anxiety in patients with Chronic Hypertension Disease.